Revision of the genus Eugenys Quate, 1996 (Diptera: Psychodidae), with the description of three new species - Jaume-Schinkel, Santiago; Kvifte, Gunnar Mikalsen (European Journal of Taxonomy, 2024)
We review the diagnosis of the genus Eugenys Quate, 1996 (Diptera: Psychodidae) which occurs in the Neotropical Region. Initially known from Costa Rica, Nicaragua, and Panama, we describe one additional species from Costa Rica, Eugenys singularis sp. nov., and two species from Ecuador, namely, Eugenys micra sp. nov. and E. upsilon sp. nov., bringing the total known species to six. This study provides detailed descriptions of the new species based on male and female specimens, along with the first DNA barcodes for the genus and some of the newly described species. We also provide an identification key for identifying male specimens of the genus worldwide. Finally, we discuss the morphological characteristics of Eugenys and compare the genus with other taxa, tentatively suggesting a placement within the tribe Pericomaini.